Review of the medicinal use of Rhaphiodon echinus Schauer (Lamiaceae): biological and pharmacological activities (Research, Society and Development, 2021)
The objective was to conduct a literature review on the biological and pharmacological activities of Rhaphiodon echinus. This is an integrative review guided by the following question: What is the scientific evidence about the biological and pharmacological activity of R. echinus? The databases MEDLINE, PUBMED, BDENF, SCOPUS and WoS were chosen for the search. A population of 54 studies was identified whose sample was characterized by nine articles. It is suspected that the essential oil and the ethanolic and aqueous extracts of R. echinus have chemical compounds of relevance in phytochemical and pharmacological tests, showing antioxidant and anti-inflammatory activities, besides antimicrobial activity against Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa by potentiating the action of drugs such as gentamicin and ciprofloxacin, as well as antifungal activity against Candida albicans. Furthermore, the phytotherapeutic activity of R. echinus in teas, syrups and baths is observed against uterine inflammation, influenza, intestinal colic and urinary tract infection. In summary, it is emphasized that new studies involving R. echinus are needed in the area of ethnobotany in order to better understand its use and interfaces with popular knowledge with a view to its use in clinical practice.